TRANSFORMASI SOSIO – SPASIAL BERBASIS PARIWISATA DI DESA TEMUKUS - Wahyuningsih, Nyoman Tri; Citra, I Putu Ananda; Christiawan, Putu Indra (International Journal of Natural Science and Engineering, 2017)
The research was conducted in Temukus Village, which aims to: (1) analyze the physical transformation based on tourism, (2) analyze the socio-economic transformation based on tourism. This research uses qualitative research. The number of subject sample to 53 house hold. Which determined by purposive sampling. Data collecting using observation technique, interview, and documentation The data are analyzed by qualitative technique. The result of research indicate that: (1) there is a physical transformation of tourism accomodation in Temukus village from 2012 and 2016 that aqual to 105% which is categorized high,  and infrastructure transformation in the long road change of 204% which are categorized as high. The high physical transformation is due to the increasing number of investors or private parties who want to build tourism accommodation, as well as the many people who sell land, especially agricultural land that will be used for the construction of tourism accommodation in Temukus Village. (2) There is a socio-conomic transformation of livelihoods change in Temukus Village from 2012 and 2016 a mounted to 85.21% which is categorized high, while revenue transformation from 2012 and 2016 is 22.24% which categorized as low. The transformation Livelihoods that categorized high due to the increasing number of Temukus village who are involved in tourism industry, in addition there are several other reasons such as the desire to change the fate. Towards the better and the desire to seek new experiences in the tourism industry.